Cost-benefit analysis of irrigation modernization in Guadalquivir River Basin - Borrego-Marín, María M.; Berbel, J. (Agricultural water management, 2019)
•Irrigation modernization is analysed at basin scale in water scarce region.•Multicriteria and cost benefit method is applied to Guadalquivir River Basin irrigation modernization.•Irrigation modernization increase the productivity value of water and regulation services.•Benefit of Irrigation modernization exceeds costs by 4.1 to 1 at Guadalquivir basin scale. In water scarce areas, policy makers frequently opt for water conservation and saving technologies (WCSTs) as a measure to ensure resource use sustainability, although this policy is subject to scientific and political debate. This paper presents an application of an integrated methodological approach for analysing the costs and benefits of using WCSTs to achieve water policy objectives. The focus is on the measures aimed at reducing irrigation water abstraction under the 1st and 2nd cycle of Water Framework Directive implementation in the Guadalquivir River Basin (Southern Spain). The method is a combination of a multicriteria assessment of the main effects of water-saving investments at basin level, estimated using a selected group of indicators. In a second stage, a cost-benefit analysis is conducted. The study finds a benefit-to-cost ratio of 4.1/1 for the Guadalquivir River Basin, thus concluding that irrigation modernization in this case study has been a good social investment. The method can be extended to other hydrological systems (aquifer basins) to draw general conclusions.